The Effectiveness of Closed Reduction Method Using Chinese Finger Trap and Immobilization of Circular Casts in the Management of Distal Radius Closed Fractures - Clement Dewanto; Zulkarnain Muslim (Sriwijaya Journal of Surgery, 2018)
ABSTRACT Introduction. Distal radius fractures are one of the most common fractures encountered by bone surgeons in the emergency room. In America, accounting for about 8% to 17% of all fracture cases that have been treated and around 75% of fractures in the forearm. In Palembang, especially in Dr. Moh Hoesin general hospital there was no data yet about the number of incidents of distal radius fractures, how to treat (conservatively or operatively) and success rates. For this reason it is difficult to measure accurately, how likely is it that a distal radius fracture can be successfully treated conservatively. Methods. This study was an observational analytic study with a longitudinal design to determine the effectiveness of closed reduction measures by immobilization casting through radiological examination in the management of cases of distal radius fractures at dr Moh Hoesin general hospital in Palembang Result. Based on the subject based on the type of fracture, there were 43.8% of subjects with Frykman-1; 6.3% of subjects with Frykman-2; 18.8% of subjects with Frykman-3; 12.5% ​​subjects with Frykman-4; 6.3% of subjects with Frykman-5; 0% of subjects with Frykman-6; 6.3% of subjects with Frykman-7; 6.3% of subjects with Frykman-8. Based on the analysis between the Fracture Type and X-Ray parameters in the form of Radial Length, Radial Inclination, Radial Tilt and Ulnar Variance, only Ulnar Variance has a significant relationship with p = 0.001 Conclusion. The effectiveness of closed reduction is significantly related to the type of Frykman fracture and the most fracture type that has been successfully closed closed is the type of Frykman I fracture with the highest number of samples and 100% success rate.